microRNA-143/145 loss induces Ras signaling to promote aggressive Pten-deficient basal-like breast cancer - Wang, Sharon (JCI Insight, 2017)
The tumor suppressor PTEN is frequently inactivated in breast and other cancers; yet, germ-line mutations in this gene induce nonmalignant hamartomas, indicating dependency on additional cooperating events. Here we show that most tumors derived from conditional deletion of mouse pten in mammary epithelium are highly differentiated and lack transplantable tumor-initiating cells (TICs) capable of seeding new tumors following orthotopic injection of FACS-sorted or tumorsphere cells. A rare group of poorly differentiated tumors did harbor transplantable TICs. These transplantable tumors exhibited distinct molecular classification, signaling pathways, chromosomal aberrations, and mutational landscape, as well as reduced expression of microRNA-143/145 (miR-143/145). Stable knockdown of miR-143/145 conferred tumorigenic potential upon poorly transplantable pten-deficient tumor cells through a mechanism involving induction of RAS signaling, leading to increased sensitivity to MEK inhibition. In humans, miR-145 deficiency significantly correlated with elevated RAS-pathway activity in basal-like breast cancer, and patients with combined PTEN/miR-145 loss or PTEN-loss/high RAS-pathway activity exhibited poor clinical outcome. These results underscore a selective pressure for combined PTEN loss together with RAS-pathway activation, either through miR-145 loss or other mechanisms, in basal-like breast cancer, and a need to identify and prioritize these tumors for aggressive therapy.